2006
DOI: 10.1007/bf02984683
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing benign from malignant gallbladder wall thickening using FDG-PET

Abstract: FDG-PET appears able to distinguish between benign and malignant gallbladder wall thickening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Some false-positive FDG-PET cases have been reported that described FDG accumulations on the gallbladder wall were observed in cases of chronic cholecystitis [16], the gallbladder tuberculosis [17], xanthogranulomatous cholecystitis [14] and Mirrizi syndrome [15]. In these cases, it appears that differentiating gallbladder cancer from benign gallbladder diseases which also exhibit wall thickness with long-term and/or extreme inflammation is very difficult.…”
Section: Discussionmentioning
confidence: 95%
“…Some false-positive FDG-PET cases have been reported that described FDG accumulations on the gallbladder wall were observed in cases of chronic cholecystitis [16], the gallbladder tuberculosis [17], xanthogranulomatous cholecystitis [14] and Mirrizi syndrome [15]. In these cases, it appears that differentiating gallbladder cancer from benign gallbladder diseases which also exhibit wall thickness with long-term and/or extreme inflammation is very difficult.…”
Section: Discussionmentioning
confidence: 95%
“…10 Gallbladder wall thickening is a nonspecific finding associated with many of these gallbladder diseases; however, the ability of F-18 FDG PET to distinguish between benign and malignant thickening has been incompletely evaluated in only a limited number of patients. 11 Uptake in the gallbladder wall may not always be related to an intrinsic gallbladder process, as rim-like FDG uptake in the gallbladder wall has been reported secondary to cholestasis/common bile duct obstruction related to a pancreatic mass. 12 Both benign and neoplastic entities can be FDG avid.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14] Many studies have evaluated the preoperative imaging diagnosis of gallbladder cancer, and reported that its differentiation from benign gallbladder diseases, such as cholecystitis and gallbladder adenomyoma, poses a diagnostic challenge. [15][16][17][18][19][20][21] On the other hand, previous studies have reported the preoperative diagnosis of gallbladder cancer by bile cytology. Recent studies have reported patients who underwent ultrasoundguided fine-needle aspiration cytology (FNAC) and achieved favorable results with a minimal risk of complications.…”
Section: Discussionmentioning
confidence: 99%